PROBLEMS OF REDUCING THE CRIMINALIZATION OF INVESTMENT ACTIVITIES OF JOINT-STOCK COMPANIES AND THEIR SOLUTIONS (American Journal of Research in Humanities and Social Sciences, 2023)
The article analyzes the relationship between the development of the shadow economy and investment activities, studies the reasons of the criminalization of investment activities of joint-stock companies, companies and organizations. Control mechanisms which are proposed to reduce the shadow component of the economy and develop investment activities.